2003
DOI: 10.1161/01.str.0000066870.70976.57
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cerebral Ischemic Preconditioning in Mice Deficient in Endothelial and Neuronal Nitric Oxide Synthases

Abstract: Background and Purpose-The purpose of this study was to test the hypothesis that nitric oxide is required for preconditioning in an intact animal model of focal ischemia using neuronal and endothelial nitric oxide synthase (nNOS and eNOS) knockout mice. Methods-Cerebral blood flow was measured in wild-type, nNOS knockout, and eNOS knockout mice by hydrogen clearance (absolute) and laser Doppler flowmetry (relative). Mice were preconditioned by three 5-minute episodes of transient middle cerebral artery occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 24 publications
4
90
0
6
Order By: Relevance
“…For example, Atochin et al (2003) have provided evidence that the endothelial (eNOS) and neuronal (nNOS) isoforms of NOS participate in the early preconditioning induced by transient cerebral ischemia, whereas eNOS may be involved in hypoxic preconditioning in a neonatal model of cerebral hypoxic-ischemic injury (Gidday et al, 1999). We recently found that nNOS and eNOS, but not iNOS, play a role in the early preconditioning induced by LPS .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Atochin et al (2003) have provided evidence that the endothelial (eNOS) and neuronal (nNOS) isoforms of NOS participate in the early preconditioning induced by transient cerebral ischemia, whereas eNOS may be involved in hypoxic preconditioning in a neonatal model of cerebral hypoxic-ischemic injury (Gidday et al, 1999). We recently found that nNOS and eNOS, but not iNOS, play a role in the early preconditioning induced by LPS .…”
Section: Discussionmentioning
confidence: 99%
“…They showed that NO production and activity were critical to the induction of ischemic tolerance and that endothelial nitric oxide synthase (eNOS), not neuronal nitric oxide synthase (nNOS) or inducible nitric oxide synthase (iNOS), was the isoform responsible for producing ischemic tolerance. In the study by Sunghee Cho and his colleagues, both inhibiting nitric oxide synthase (NOS) and scavenging NO during preconditioning significantly attenuated the induced ischemic tolerance, however, neither eNOS nor nNOS knockout mice demonstrated altered ischemic preconditioning [14,69,70] . Meanwhile, preconditioning by volatile anesthetics also appears to involve the NO pathway.…”
Section: Nitric Oxide/reactive Oxygen Species and Neuroprotectionmentioning
confidence: 99%
“…Available pharmacologic evidence is even more indicative of NO involvement in the initial mechanisms that trigger PC, with model-specific effects of various inhibitors to eliminate PC when given during the priming insult (Cho et al, 2005;Gidday et al, 1999;Puisieux et al, 2000). Failure to observe acute PC in both neuronal NOS and eNOS knockout mice (Atochin et al, 2003) or delayed protection in iNOS knockout mice (Cho et al, 2005) could reflect effects on both the development and the expression of PC. Nitric oxide is also implicated in cellular PC mechanisms (Nandagopal et al, 2001), independent of vascular effects.…”
Section: Perfusion Changes and Ischemic Preconditioningmentioning
confidence: 99%